2015
DOI: 10.1016/j.joca.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning classification of OARSI-scored human articular cartilage using magnetic resonance imaging

Abstract: Objective The purpose of this study is to evaluate the ability of machine learning to discriminate between magnetic resonance images (MRI) of normal and pathological human articular cartilage obtained under standard clinical conditions. Method An approach to MRI classification of cartilage degradation is proposed using pattern recognition and multivariable regression in which image features from MRIs of histologically scored human articular cartilage plugs were computed using weighted neighbor distance using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…We note that in our previous study, we used WND‐CHRM features computed on MRIs of osteochondral plugs to construct a multiple linear regression model for classification based on OARSI score . We found that the accuracy of binary classification based on several MR measurements, including the diffusion weighted image with b = 999 s/mm 2 and the T 2 W image with TE = 50 ms, improved through use of regression, which establishes relationships throughout the entire dataset for classification of single samples.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We note that in our previous study, we used WND‐CHRM features computed on MRIs of osteochondral plugs to construct a multiple linear regression model for classification based on OARSI score . We found that the accuracy of binary classification based on several MR measurements, including the diffusion weighted image with b = 999 s/mm 2 and the T 2 W image with TE = 50 ms, improved through use of regression, which establishes relationships throughout the entire dataset for classification of single samples.…”
Section: Discussionmentioning
confidence: 96%
“…The features computed from WND‐CHRM were used to develop a multivariable least‐squares regression model to predict OARSI scores and classify OA cartilage with up to 86% accuracy in various MR contrast modalities. Our previous in vitro results indicate the ability to non‐invasively assign individual subjects to a degree of OA pathology . One essential difference between this previous study of explants and analyses performed in the in vivo setting is the requirement for reproducible tissue segmentation in the latter.…”
mentioning
confidence: 93%
See 3 more Smart Citations